The Lure of the Tropics and the Colonial Emporium: The Study of Book Illustration and Newspaper Advertisement in Colonial North Borneo - Mohd Pakri, Mohamad Rashidi; Simon, Peter Hull; Abdul Rahim, Anis (Pusat Pengajian Ilmu Kemanusiaan, 2019)
Many historians use “Gold, God, and Glory” to describe the motives generating the overseas exploration, expansion, and conquests of the Western power over the East. In this paper, we intent to revisit those shorthands, the 3 G’s above, in rather different ways: the first part of the title of this paper, ‘The Lure of the Tropics and the Colonial Emporium” could be used to summarise similar colonising motives of the West. The ‘lure’ indicates the temptation the colonial officers faced in the tropics, and this indication serves as an interpellation of colonial ideology, which makes use of the tropics and its inhabitants (i.e. colonised people) as its consumers and seize control of the means of production. Hence, the second part of the title, ‘The Book Illustration and Newspaper Advertisement’ would serve as a few examples of how the natives are being treated as well as how the colonial advertisement messages help to promote the idea of selling western products in the tropics vis-à-vis colonial emporium respectively.